(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article is devoted to the advantages and disadvantages of CLT method in teaching foreign language and to develop especially learners speaking skills. It considers an overview of the development in Foreign Language Teaching for real communication rather than learning systems of grammar and vocabulary. Recently, most of teaching instructors are focuses more on the process of teaching, and understanding how to create lessons drawing on whatever you have been taught, whatever teaching context is and ever whatever you have come up with on own as a basis for teaching practice.